Does Implicit Self-Reference Effect Occur by the Instantaneous Own-Name? - Yaoi, Ken; Osaka, Mariko; Osaka, Naoyuki (Frontiers in Psychology, 2021)
Self-reference effect (SRE) is defined as better recall or recognition performance when the materials that are memorized refer to the self. The SRE paradigm usually requires participants to explicitly refer items to themselves, but some researchers have found that the SRE also can occur for implicitly self-referenced items. Few studies though have investigated the effect of self-related stimuli without awareness. In this study, we presented self-related (participants’ names) or other (other’s names or nouns) stimuli for a very short time between masks and then explicitly presented subsequent trait adjectives to participants. Recognition performance showed no significant differences between the own-name and the other two conditions in Experiment 1 that had random-order conditions. On the other hand, the result of Experiment 2 that had block-order conditions and greater prime stimuli suggests that SRE can occur as a result of the instantaneous stimulus: Subjects who showed better memory performance also had relatively high recognition of the trait adjectives that they viewed after their instantaneously presented own-name. This effect would show that self-representation can be activated by self-related stimuli without awareness and that subsequent items are unconsciously referenced to that self-representation.